(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2022)
The main criteria of oil and gas bearing capacity within oil-producing areas and promising regions are highlighted, depending on the peculiarities of their geological. Regional and local traps were analyzed and deposits were discovered in oil-gas areas. Installed the most favorable conditions for the formation of large and medium oil and gas deposits. It was established that the main criteria of oil and gas capacity are determined by the structural, tectonic, lithological and facies conditions of the territorial development. The regularities of the detection of traps and deposits are related to the nature of the tectonics of the region. The most favorable conditions for the formation of reservoir rocks and deposits of oil and gas within large structures belong to paleo uplifts. An important conclusion was made about the most promising areas within oil and gas industrial areas.